2022
DOI: 10.1108/bpmj-11-2021-0713
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the link between knowledge management capability and innovation ambidexterity: organizational structure as a moderator

Abstract: PurposeThis study examines the relationship between knowledge management (KM) capability and innovation ambidexterity, and their subsequent influence on firm performance. It also investigates whether organizational structure – in terms of connectedness and centralization – helps to develop a suitable context that either hinders or catalyzes the effectiveness of KM capability in predicting innovation ambidexterity.Design/methodology/approachData were collected from 336 manufacturing organizations in Pakistan us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 106 publications
0
10
0
1
Order By: Relevance
“…'s (2022) study concerning the impact of knowledge sharing on innovation ambidexterity, it was in harmony with the work of Rialti et al. (2020) on strategic flexibility and Shafique et al. 's (2022) study on KMC as an instrumental and significant enabler for achieving innovation exploration and exploitation in Pakistani firms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…'s (2022) study concerning the impact of knowledge sharing on innovation ambidexterity, it was in harmony with the work of Rialti et al. (2020) on strategic flexibility and Shafique et al. 's (2022) study on KMC as an instrumental and significant enabler for achieving innovation exploration and exploitation in Pakistani firms.…”
Section: Discussionmentioning
confidence: 77%
“…Alshawabkeh et al (2020), based on data collected from 350 senior managers in Jordanian manufacturing firms, emphasised the mediating role of innovation ambidexterity between KMC and project success. Similarly, Shafique et al (2022) reported innovation ambidexterity as a mediator between KMC and firms' performance when analysing data collected from 336 manufacturing firms. Accordingly, the present study developed the following hypothesis: H10.…”
Section: The Mediating Effectsmentioning
confidence: 99%
“…We have demonstrated that by improving the MGS and the decision-making process, and by articulating appropriate planning, it is possible for organizations to strengthen their innovation capability. This idea has received support from different studies (Ali et al , 2017; Shafique et al , 2022; Behl et al , 2023).…”
Section: Resultsmentioning
confidence: 95%
“…The proposed relationships between KM capabilities, innovation ambidexterity and organizational structure were further evident in a study by Shafique et al (2022) of firms operating within different manufacturing industries in Pakistan. Study context was determined by the nation’s status as an emerging economy and emergence from years of sociopolitical turmoil.…”
Section: Pakistan Study and Findingsmentioning
confidence: 84%